Solid-state methods for processing synthetic thermoplastic articles.
Patent Information
- Application Number
- JP2024565895
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-01-25
- Filing Date
- 2023-01-17
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2043-01-17
Smart Images

Figure 2025504701000001 
Figure 2025504701000002 
Figure 2025504701000003
Abstract
Description
[Technical field]
[0001] The present invention relates generally to methods for treating synthetic thermoplastic articles. [Background technology]
[0002] Synthetic thermoplastics such as aliphatic polyamides (commonly known as "nylon"), polyesters and polyacrylonitrile (PAN) are used, among other purposes, to produce fibers and yarns which are subsequently knitted or woven to produce fabrics. Polyamide fabrics are notable for their high strength and abrasion resistance. Polyamide, polyester and PAN fabrics are useful for producing clothing and protective equipment for military, paramilitary and law enforcement personnel. These fabrics are also used to produce a variety of products for use inside homes, offices and / or other buildings, including, among other things, carpets, drapes and curtains, furniture upholstery, bedding, shower curtains, window treatments, wallpaper and other decorative coverings.
[0003] Being thermoplastic materials, polymers such as polyamides, polyesters and PAN are capable of heat softening and flowing when heated to a sufficiently high temperature. In at least some of the aforementioned applications, it is important to prevent dripping when the article is exposed to an open flame or other heat source. This is often a fire safety issue, as dripping burning material can cause injury or death by spreading flames or dripping on people or animals. This concern is reflected in various standard fire tests, such as ASTM D6413-11, EN 13501-1 Single Burning Item test and British Standard BS5867 Part 2-Type B test, which evaluate for droplet formation under specific ignition conditions.
[0004] Many strategies have been devised to improve the performance of thermoplastic articles in standardized fire tests. They often involve the inclusion of various additives such as char formers, organophosphorus compounds, organohalogen compounds, hydrated minerals, red phosphorus, and borates. All of these additives have drawbacks. They increase costs, require additional processing steps, affect physical and / or aesthetic properties, and in some cases pose exposure or environmental risks. Most have little effect on melting and / or dripping.
[0005] Molded nylon parts can be crosslinked by compounding thermoplastic nylon with polyene compounds (such as triallyl cyanurate, triallyl isocyanurate, and trimethylolpropane trimethacrylate) and then irradiating the compounded material in the mold. See, for example, J. Am. Chem. Soc. 1999, 143: 1311-1323. In principle, melting and / or dripping can be reduced by crosslinking thermoplastic polymers, but this process is not compatible with the production of fibers or fabrics on an industrial scale. Similarly, polymers have been crosslinked or branched using combinations of such polyene compounds with various free radical initiators. This is described, for example, in J. Am. Chem. Soc. 1999, 143: 1311-1323 and J. Am. Chem. Soc. 1999, 143: 1311-1323. These methods are carried out in the melt. They are not compatible with the production of industrial fibers or yarns, since they produce a significant amount of gels. These gels clog the spinnerets and cause fiber breakage during the spinning and / or subsequent drawing steps. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] International Publication No. 2019 / 152264 [Non-patent literature]
[0007] [Non-Patent Document 1] Pramanik et al., Radiation Physics and Chemistry,2009,Vol.79,p.199-205 [Non-Patent Document 2] Yang et al., Polymer Testing, 2008, Vol. 27, p. 957-963 DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] The present invention is a solid-state method for treating a synthetic thermoplastic article comprising a synthetic thermoplastic component, the synthetic thermoplastic component comprising one or more synthetic thermoplastic resins having a crystalline melting temperature of 100° C. or greater. a) applying a coating composition to one or more surfaces of the article and contacting one or more polyamide and / or polyester components of the article at a temperature below the crystallization temperature of the synthetic thermoplastic resin, the coating composition comprising: (i) one or more polyene compounds having 2 to 6 vinyl groups and a vinyl equivalent weight of 125 g / eq or less; and (ii) one or more free radical initiators, the coating composition being applied to the article in an amount sufficient to provide at least 0.04 kg of polyene compound and at least 0.005 kg of peroxy or azo free radical initiator per kg of synthetic thermoplastic component in the article; b) heating the coated article to a temperature of at least 70° C. and below the crystalline melting temperature of the synthetic thermoplastic resin to decompose the peroxy or azo free radical initiator to form free radicals and produce crosslinks in the aliphatic synthetic thermoplastic resin.
[0009] Very surprisingly, the applicant has found that it is possible to induce crosslinking in synthetic thermoplastics by topically applying a coating composition followed by a heating step in the solid state (i.e. below the crystalline melting temperature of the synthetic thermoplastics). The ability to crosslink in this manner offers very substantial advantages. It is no longer necessary to melt blend the crosslinking agent (polyene and free radical initiator) into the synthetic thermoplastics before producing the article. Special grades of resin are therefore not required and the compounding costs to produce them are avoided. A radiation treatment step, as described in Non-Patent Document 1, is no longer necessary and can therefore be eliminated. Simple and inexpensive coating and heating equipment can be used. The process is adaptable to both continuous and batch operations and can therefore often be implemented in existing production lines.
[0010] The process actually allows synthetic thermoplastic articles produced using melt processing methods such as melt spinning, extrusion, blow molding, etc. to be modified in a simple manner to produce properties in the article (or at least on the treated surface) that are more similar to those of crosslinked thermosetting polymers that are otherwise not available for melt processing operations. One particular advantage is that the treated products generally show reduced or even eliminated melting and / or dripping when exposed to flame in a vertical flame test. This is an important advantage when the article is a fabric or sheet material that constitutes or forms part of personal clothing, protective equipment, and architectural, furniture, or decorative products.
[0011] The process of the present invention typically does not affect the dimensions or geometry of the article, and changes in size and shape as a result of the process are negligible or in some cases non-existent.
[0012] In a second aspect, the invention is a solid-state method for reducing melting, dripping, or both, of a fabric comprising fibers made from a synthetic thermoplastic resin having a crystalline melting temperature of 100° C. or greater, either alone or in a blend with fibers made from a polymer other than a synthetic thermoplastic resin having a crystalline melting temperature of 100° C. or greater, the fibers having a melting temperature of 100° C. or greater as measured according to ASTM D7138-16, the method comprising the steps of: a) applying a coating composition to one or more surfaces of the fabric at a temperature below the melting temperature of the fibers, the coating composition comprising: i) from 30 to 99.9 weight percent, based on the weight of the coating composition, of one or more polyene compounds having 2 to 6 vinyl groups and a vinyl equivalent weight of 125 g / eq or less; and (ii) one or more free radical initiators, wherein a sufficient amount of the coating composition is applied to the article to provide at least 0.04 kg of polyene compound and at least 0.005 kg of peroxy or azo free radical initiator per kg of fabric; b) heating the coated fabric to a temperature of at least 70° C. and below the melting temperature of the fibers for a period of 1 minute to 2 hours.
[0013] The fabric remains flexible and soft after treatment, and in particular the fibers or filaments do not clump together to form large clumps. Little or no change in tactile properties (sometimes referred to as "hand") is observed. Air flow is substantially unchanged or only slightly altered.
[0014] A further advantage of the present invention is that the coating composition may further comprise additional ingredients that provide beneficial effects, such as, for example, plasticizers, fabric softeners, dyes, hydrophobic and / or oleophobic treatments, and many others.
[0015] The process is particularly suitable for treating aliphatic polyamide, polyester and / or PAN fabrics, which may, for example, comprise aliphatic polyamide, polyester or PAN fibers alone or in blends with each other and / or with fibers of one or more other polymers other than polyamide, polyester or PAN, the fibers of such other polymers having a melting temperature of 100° C. or more as measured according to ASTM D7138-16.
[0016] The article to be treated includes one or more synthetic thermoplastic components including one or more synthetic thermoplastic resins having a crystalline melting temperature of 100° C. or greater. Examples of such synthetic thermoplastic resins include polyamides, polyesters, and PAN. In some embodiments, the synthetic thermoplastic resins comprise 50% or more, 75% or more, or 90% or more of the total weight of the synthetic thermoplastic component.
[0017] In some embodiments, the synthetic thermoplastic resin is or comprises a polyamide. A polyamide is aliphatic, i.e., does not contain aromatic groups. It is a thermoplastic organic polymer with repeat units linked by amide bonds. The formula molecular weight per amide group is preferably 500 g / mol or less, preferably 300 g / mol or less. The polyamide has a crystalline melting temperature of 100° C. or more, preferably 150° C. or more, as measured according to the capillary method of ISO 3146:2000. The polyamide may be a polymer of α,ω-amino acids, a copolymer of a dicarboxylic acid and a diamine, a polymer of a cyclic lactam, or a combination of any two or more thereof. Examples of useful polyamides include nylon 4, nylon 6, nylon 8, nylon 9, nylon 10, nylon 12, nylon 4 / 6, nylon 5 / 6, nylon 6 / 6, nylon 6 / 9, nylon 10 / 10, and nylon 10 / 12.
[0018] In another embodiment, the synthetic thermoplastic resin is or includes a polyester. The polyester may or may not contain aromatic groups. It is a thermoplastic polymer having repeating units linked by ester bonds. The formula molecular weight per ester group is preferably 500 g / mol or less, preferably 300 g / mol or less. The polyester has a crystalline melting temperature of 100° C. or more, preferably 150° C. or more, as measured according to the capillary method of ISO 3146:2000. The polyester may be, for example, but is not limited to, poly(ethylene terephthalate), poly(butylene terephthalate), poly(ethylene adipate-co-terephthalate), poly(butylene adipate-co-terephthalate), poly(ethylene succinate), poly(1,4-cyclohexylene-dimethylene terephthalate), or poly(butylene succinate).
[0019] In yet other embodiments, the synthetic thermoplastic resin is or includes poly(acrylonitrile). The synthetic thermoplastic component may contain other materials in addition to the synthetic thermoplastic resin, which may include, for example and without limitation, other polymers that are blended with or form dispersions with the synthetic thermoplastic resin, fillers and reinforcing agents, rheology modifiers, impact modifiers, plasticizers, colorants, various thermoplastic processing aids (such as lubricants), preservatives, biocides, antioxidants and UV stabilizers, among many others.
[0020] The article may include one or more components that do not contain synthetic thermoplastic resins. Such other components may be attached to the synthetic thermoplastic component, for example, with an adhesive, mechanically, magnetically, or otherwise. For example, the article may be a multi-layer structure having one or more layers of synthetic thermoplastic resin and one or more other layers that do not contain any synthetic thermoplastic resins.
[0021] Articles of particular interest include fabrics having fibers (especially one or more aliphatic polyamide fibers, polyester fibers, and PAN fibers) made of one or more synthetic thermoplastics having a crystalline melting temperature of 100° C. or higher. Such fabrics include fibers and / or yarns made of synthetic thermoplastics that are woven, knitted, entangled, knotted, felted, melt bonded, or glued together. Fibers or yarns made of synthetic thermoplastics having a crystalline melting temperature of 100° C. or higher may be blended with other fibers or yarns made of other materials that are not synthetic thermoplastics having a crystalline melting temperature of 100° C. or higher. Such other fibers may be or include fibers made of materials such as cotton, elastomeric polyurethanes (including spandex), cellulose, wool, silk, aramid, polypropylene, polyacetate, cellulose esters (such as rayon), and the like. The fibers have a melt temperature of 100° C. or greater, preferably 150° C. or greater, according to ASTM D7138-16, Method A (for blends of two or more different fibers) or Method B (for monocomponent fibers). The fabric may be in the form of a roll good which may have a width of 100 mm or greater (e.g., from 300 mm to 7 meters or greater), or may comprise all or part of a finished article, such as articles such as clothing, curtains, bedding, carpets, wall coverings, or both.
[0022] In step a) of the process, a coating composition for one or more surfaces of the article is contacted with one or more synthetic thermoplastic components of the article. The coating composition comprises i) one or more polyene compounds having 2 to 6 vinyl groups and a vinyl equivalent weight of 150 g / eq or less, and (ii) one or more free radical initiators. The coating composition is advantageously in the form of a liquid or a dispersion having a liquid phase containing dispersed solids at the temperature at which it is applied to the article. If it is a dispersion, the polyene compound and the free radical initiator may each independently be present in the liquid phase or in the solid phase, or partially in both. The liquid phase of the dispersion may be, for example, the polyene compound or the free radical initiator, or both, and alternatively or additionally, the liquid phase may be or may include a carrier or other functional component. In some embodiments, the coating composition is a dispersion of solid free radical initiator particles in a liquid phase that includes a liquid polyene compound and, optionally, one or more other liquid components, such as a carrier and / or other liquid functional components.
[0023] The polyene compound contains 2 to 6 vinyl groups per molecule. A "vinyl" group for the purposes of the present invention is a -CHR=CHR group, where each R is independently hydrogen, a linear, branched or cyclic alkyl having up to 6 carbon atoms, or phenyl. The vinyl group is preferably an allylic group (i.e., part of a larger group having the form -CH2-CHR=CHR), an enone group (i.e., part of a larger group having the form -C(O)-CHR=CHR), or both. R is preferably hydrogen in each instance.
[0024] In some embodiments, each polyene compound (if more than one) contains from 2 to 4 vinyl groups per molecule, and in certain embodiments, 2 or 3 vinyl groups per molecule.
[0025] Each polyene compound may have a vinyl equivalent weight of 125 g / equivalent or less. Examples of suitable polyene compounds include various compounds corresponding to esters of acrylic or methacrylic acid with polyols, such as, for example, 1,4-butanediol diacrylate, 1,5-pentanediol diacrylate, 1,6-hexanediol diacrylate, neopentyl glycol diacrylate, diethylene glycol diacrylate, triethylene glycol diacrylate, tetraethylene glycol diacrylate, polyethylene glycol diacrylate, dipropylene glycol diacrylate, tripropylene glycol diacrylate, cyclohexanedimethanol diacrylate, alkoxylated hexanediol diacrylate, neopentyl glycol diacrylate, propoxylated neopentyl glycol diacrylate. Suitable acrylate compounds include tris(2-hydroxyethyl)isocyanurate triacrylate oligomers, ...
[0026] Other suitable polyene compounds are compounds containing two or more allyl groups. Examples of these include polyallyl ethers of polyols and polyallyl esters of polycarboxylic acids. Suitable polyallyl ethers are, for example, 1,4-butanediol diallyl ether, 1,5-pentanediol diallyl ether, 1,6-hexanediol diallyl ether, neopentyl glycol diallyl ether, diethylene glycol diallyl ether, triethylene glycol diallyl ether, tetraethylene glycol diallyl ether, polyethylene glycol diallyl ether, dipropylene glycol diallyl ether, tripropylene glycol diallyl ether, cyclohexanedimethanol diallyl ether, alkoxylated hexanediol diallyl ether, neopentyl glycol diallyl ether, propoxylated ne These include pentyl glycol diallyl ether, trimethylolpropane di- or triallyl ether, ethoxylated trimethylolpropane di- or triallyl ether, propoxylated trimethylolpropane di- or triallyl ether, glycerin di- or triallyl ether, ethyloxylated and / or propoxylated glycerin di- or triallyl ether, pentaerythritol di-, tri-, or tetra-allyl ether, erythritol di-, tri-, or tetra-allyl ether, acrylated polyester oligomer, bisphenol A diacrylate, acrylated bisphenol A diglycidyl ether, ethoxylated bisphenol A diallyl ether, and the like.
[0027] Examples of suitable polyallyl esters include diallyl maleate, diallyl fumarate, diallyl phthalate, diallyl terephthalate, diallyl succinate, di- or triallyl citrate, and the like.
[0028] Other useful polyene compounds include triallyl cyanurate and triallyl isocyanurate (TAIC). The free radical initiator is one or more compounds that thermally react and / or decompose under the conditions of step b) of the process to generate free radicals. Free radical initiators that are solid at 22° C. are preferred, as are free radical initiators that have a 10-hour half-life temperature (as reported by the manufacturer of the free radical initiator) of 30 to 70° C. or more, and especially 80 to 120° C., when measured in toluene. The free radical initiator is preferably soluble in water to an extent of 1 gram per liter of water or less, and soluble in toluene to an extent of 25 grams per liter of toluene or more.
[0029] Azo free radical initiators have been found to be particularly useful. Azo free radical initiators include the moiety RN=N-R', where R and R' are organic groups that form carbon-nitrogen bonds to their respective adjacent nitrogens. Examples of azo free radical initiators include 2,2'-azobisisobutyronitrile (AIBN), 2,2'-azobis(2,4-dimethylpentanenitrile), 4,4'-azobis(4-cyanovaleric acid), 1,1'-azobis(cyclohexane-1-carbonitrile), 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile) and 2,2'-azobis(2-methylbutyronitrile).
[0030] Other useful free radical initiators include, for example, 1) acyl peroxides (e.g., acetyl peroxide or benzoyl peroxide), 2) alkyl peroxides (e.g., cumyl peroxide, dicumyl peroxide, lauroyl peroxide, or t-butyl peroxide), 3) hydroperoxides (e.g., t-butyl hydroperoxide or cumyl hydroperoxide), 4) peresters (e.g., t-butyl perbenzoate), 5) other organic peroxides (e.g., acyl alkylsulfonyl peroxides, dialkyl peroxydicarbonates, diperoxyketals, or ketone peroxides), 6) cyclic ketones and 1,2,4-trioxepanes (described, for example, in U.S. Pat. No. 8,334,348), 7) azide compounds, 8) various tetrazines, and 9) various persulfate compounds (e.g., potassium persulfate).
[0031] The polyene compound may, for example, comprise 30% to 99.9% of the total weight of the coating composition. In certain embodiments, the polyene compound comprises 35% or more, 40% or more, 45% or more, or 50% or more of the total weight of the coating composition. In other certain embodiments, the polyene compound comprises up to 99.5%, up to 99%, up to 95%, up to 80%, up to 70%, or up to 50% of the total weight of the coating composition.
[0032] The free radical initiator may, for example, comprise 0.1% to 50% of the total weight of the coating composition. In certain embodiments, the polyene compound comprises 0.5% or more, 1% or more, 2% or more, 3% or more, or 4% or more of the total weight of the coating composition. In other certain embodiments, the polyene compound comprises up to 25%, up to 15%, up to 10%, up to 7.5%, or up to 6% of the total weight of the coating composition.
[0033] In some embodiments, the polyene compound and the free radical initiator collectively comprise 35% or more, 45% or more, 50% or more, 60% or more, or 75% or more of the total weight of the coating composition, up to 100%, up to 98%, or up to 90% thereof.
[0034] In some embodiments, the coating composition further comprises one or more terminal vinyl polysiloxanes. The polysiloxanes may have a vinyl content of, for example, 0.05 mmol / gram or more, 0.1 mmol / gram or more, and up to 2 mmol / gram, preferably up to 1 mmol / gram, or up to 0.5 mmol / gram. The polysiloxanes may contain 2 or more vinyl groups or 3 or more vinyl groups per molecule, and up to 10 vinyl groups per molecule, and may have a vinyl content of 6 mm or more. 2 / s~1000mm 2 Such vinyl terminated polysiloxane products are available from AB Specialty Silicones under the Andisil® trade name. When present, such vinyl terminated polysiloxanes may comprise, for example, 5% or more, 10% or more, or 20% or more, and up to 69.9%, up to 60%, up to 50% of the total weight of the coating composition.
[0035] In certain embodiments, the coating composition comprises 30-60% by weight, particularly 35-65% by weight, of a polyene compound, 2-10% by weight of a free radical initiator, and one or more vinyl-terminated polysiloxanes having a vinyl content as described above of 25-75% by weight. These three components may collectively comprise, for example, 45%-100% or 70%-100% of the total weight of the coating composition.
[0036] The coating composition may contain other ingredients different from the aforementioned polyene compound, free radical initiator, and vinyl-terminated polysiloxane, which may function as carriers (i.e., to provide or replenish the liquid phase) and / or perform other specific functions.
[0037] Useful carriers or mixtures of carriers are materials that are liquid at 22° C. or solid at 22° C. but have a melting temperature of 70° C. or less, preferably 50° C. or less. The carrier also preferably has a boiling point of 100° C. or more, more preferably 125° C. or more, even more preferably 150° C. or more. Examples of useful carriers include (i) aliphatic monoalcohols or aliphatic monocarboxylic acids having 14 to 30 carbon atoms; (ii) esters of fatty acids and aliphatic alcohols, the esters having 18 to 48 carbon atoms, preferably 20 to 36 carbon atoms; (iii) polyethers having one or more hydroxy groups; (iv) polysiloxanes other than vinyl terminated, which may be linear, branched or cyclic; (v) polysiloxane-poly(alkylene glycol) copolymers; (vi) waxes, such as polyethylene wax, beeswax, lanolin, carnauba wax, candelilla wax, olicuric wax, sugarcane wax, jojoba wax, epicuticular wax, coconut wax, petroleum wax, paraffin wax, and the like; (vii) fluoropolymers; (viii) solid vegetable and / or animal oils or fats; (viii) other organic oligomers or polymers having a pure phase melting or softening point of up to 100° C.; or (ix) various plasticizers.
[0038] Aliphatic monoalcohols include fatty alcohols, including saturated fatty alcohols such as 1-dodecanol, 1-tetradecanol, 1-hexadecanol, 1-octadecanol, etc., which have one or more carbon-carbon unsaturation sites in the fatty alcohol chain. Useful esters of fatty acids and fatty alcohols include, for example, hexyl octadecanoate, octyl octadecanoate, dodecyl octadecanoate, hexadodecyl octadecanoate, etc. The fatty acid and / or fatty alcohol portion of the ester may contain one or more carbon-carbon unsaturation sites.
[0039] Suitable polyethers are polymers of one or more cyclic ethers, such as propylene oxide, tetramethylene glycol, etc. The molecular weight is high enough to produce a polymer with a melting point of up to 100° C. The polyether may contain one or more hydroxy groups. It may be linear or branched. The polyether may contain terminal alkyl ester groups. Specific examples of suitable polyethers include poly(ethylene oxide), monoalkyl esters of poly(ethylene oxide), poly(propylene oxide), monoalkyl esters of poly(propylene oxide), copolymers of ethylene oxide-propylene oxide and their monoalkyl esters, poly(tetramethylene oxide), etc.
[0040] Useful polysiloxanes include, for example, poly(dimethylsiloxane) and its copolymers. The polysiloxanes may be linear, branched or cyclic. Useful siloxane-poly(alkylene glycol) copolymers include, for example, poly(dimethylsiloxane-poly(ethylene glycol) copolymers, which may have block or graft structures. Particularly preferred polysiloxanes include octamethylcyclotetrasiloxane, decamethylcyclopentasiloxane, and linear or branched polydimethylsiloxane (PDMS) oils, polymethylhydrosiloxane (PMHS) oils, and other liquid cyclomethicones.
[0041] Paraffin or beeswax are particularly preferred wax carriers. Stearyl and cetyl alcohols are particularly preferred alcohol carriers and are solids at 22°C. Plasticizers include phthalates, trimellitates, adipates, maleates, benzoates, terephthalates, various fatty acid esters, epoxidized vegetable oils, sulfonamides, organic phosphates, alkyl citrates, and acetylated monoglycerides.
[0042] The carrier may provide certain functional contributions to the cured composition. In some embodiments, the carrier provides increased hydrophobicity and / or oleophobicity to the cured composition. It may also perform a plasticizing function. The carrier does not increase flammability.
[0043] The carrier may also include low molecular weight organic compounds having a boiling point below 100° C. and no polymerizable unsaturation (i.e., not monomeric as described above). These low molecular weight organic compounds include, for example, liquid polyethers, polyether monoalkyl esters, such as PPG-14 monobutyl ester; liquid alkanes, such as n-hexane, n-pentane, n-heptane, henicosane, docosane, tricosane, tetracosane, pentacosane, hexacosane, heptacosane, octacosane, nonacosane, and triacontane; liquid alcohols, such as n-propanol, isopropanol, n-butanol, t-butanol, methanol, and ethanol; fluorinated alkanes, such as perfluorohexane, perfluoroheptane, perfluorodecane-pinane, perfluorodecane-octane, and perfluorododecane; chlorinated alkanes, such as isoamyl chloride, isobutyl chloride, and benzyl chloride. Liquid fatty acids include, but are not limited to, alkanes and chlorinated aromatics; alkanediols and polyalkylene glycols such as ethylene glycol, propylene glycol, diethylene glycol, triethylene glycol, dipropylene glycol, tripropylene glycol, and 1,4-butanediol; liquid esters such as diisopropyl sebacate and glycerol tripalmitate; ketones such as acetone and methyl ethyl ketone; liquid fatty acids such as stearic acid, oleic acid, palmitic acid, and lauric acid; 1-naphthalamine; biphenyl; benzophenone; diphenylamine; 1,2-diphenylethane; maleic anhydride; pyrazine; thymol; glycerin; sorbitol or other sugars; and dibenzylidene sorbitol.
[0044] Carriers, when present, may comprise up to 64.9% of the total weight of the coating composition. However, such carriers are preferably present in significantly lower amounts, if at all. Preferred upper amounts are up to 50%, up to 25%, or up to 10%.
[0045] Other examples of such other components include one or more free radical curable monomers with exactly one free radical polymerizable group per molecule and a molecular weight of up to 500. Examples of such monomers have one or more hydrocarbyl groups with 8 or more carbon atoms and / or one or more siloxane groups directly or indirectly bonded to the polymerizable group. The hydrocarbyl groups may be partially fluorinated or perfluorinated. The free radical polymerizable group may be any that polymerizes in a free radical polymerization, but is preferably a vinyl, acrylate, methacrylate or chlorosilane group. The solubility of the monomer in water at 30° C. is preferably 2 parts by weight or less, more preferably 1 part by weight or less, and even more preferably 0.25 parts by weight or less per 100 parts by weight of water. Water is soluble in the monomer to an extent of preferably 2 parts by weight or less, more preferably 1 part by weight or less, and more preferably 0.25 parts by weight or less per 100 parts by weight of monomer at 30° C. Examples of such monomers are further described in WO2015 / 127479. Specific examples of monomers include, but are not limited to, one or more of the following: octyl acrylate, octyl methacrylate, decyl acrylate, decyl methacrylate, lauryl acrylate, lauryl methacrylate, octadecyl acrylate, octadecyl methacrylate, 2-(perfluorohexyl)ethyl acrylate, 2-(perfluorooctyl)ethyl acrylate, 2-(perfluorodecyl)ethyl acrylate, 2-(perfluorohexyl)ethyl methacrylate, 2-(perfluorooctyl)ethyl methacrylate, lauryl methacrylate, stearyl methacrylate, 2-(perfluorodecyl)ethyl methacrylate, 2-(perfluorooctyl)ethyl trichlorosilane, vinyl siloxane, and vinyl naphthalene.
[0046] The coating composition may further contain one or more blowing agents. Suitable blowing agents include physical (endothermic) types that are liquid at 22°C but volatilize under the conditions of the curing process, and physical types that react to form a gas, e.g., decompose under the conditions of the curing reaction. Organic physical blowing agents, when present, are used in small amounts such that the curable composition contains no more than 10% by weight, preferably no more than 5% by weight, more preferably no more than 2% by weight, even more preferably no more than 1% by weight, and even more preferably no more than 0.25% by weight of organic compounds with a boiling point below 100°C. Chemical blowing agents preferably produce carbon dioxide or nitrogen. Chemical blowing agents include the so-called azo types, peroxy blowing agents (peroxy esters, peroxy carbonates, etc.), as well as certain carbamate and citrate compounds.
[0047] The curable composition can be prepared by simply mixing the components. The order of addition is generally not important, unless exposed to temperatures at which the free radical initiator decomposes. The preferred method of forming the composition is to combine them in any order at a temperature between 10°C and 50°C with stirring.
[0048] The coating composition is applied to the article and contacts one or more synthetic thermoplastic components of the article. It can be applied using any of many convenient methods, such as by rolling, brushing, spraying, dipping the article in the composition, applying a paddle, rubbing the composition into the surface of the article using, for example, an air knife or doctor blade. A particularly useful method of applying it, especially in a continuous industrial process, is to spread it on the article using a roller. The curable composition in such a case is applied to the roller in any convenient manner and transferred to the substrate by contacting the substrate with the roller.
[0049] The application temperature (i.e., the temperature of the article at the time of application) is below the crystalline melting temperature of the synthetic thermoplastic resin or, in the case of fabrics, below the melting temperature of the fibers as measured according to the applicable method of ASTM D-7138-16. It is important that the article remains in a solid state throughout the process. The application temperature is preferably 70°C or less, more preferably 50°C or less or 35°C or less. An especially preferred application temperature is between 10 and 35°C.
[0050] The amount of coating applied can be expressed in terms of the weight of the article and / or in terms of its surface area to which the coating composition is applied. In some embodiments, the amount of coating composition is sufficient to provide 0.04 kg to 0.75 kg of polyene compound per kg of synthetic thermoplastic component in the article, and 0.005 kg to 0.05 kg of peroxy or azo free radical initiator per kg of synthetic thermoplastic component in the article. If the coating composition is applied to multiple sides of the article, the aforementioned weights apply to the combined weight of polyene compound and peroxy or azo free radical initiator in all of the applied coatings. The amount of coating composition may be sufficient to provide 0.05 kg or more, 0.06 kg, 0.075 kg or more, or 0.9 kg or more of polyene compound and 0.006 kg or more of peroxy or azo free radical initiator per kg of synthetic thermoplastic component in the article. In some embodiments, the amount of coating composition is selected to provide 0.6 kg or less, 0.4 kg or less, or 0.3 kg or less of polyene compound and 0.04 kg or less, or 0.03 kg or less of peroxy or azo free radical initiator per kg of synthetic thermoplastic component in the article. The total weight of the coating composition may be, for example, from 0.05 kg to 1 kg, especially from 0.075 kg to 0.5 kg, of coating composition per kg of synthetic thermoplastic component in the article.
[0051] The coated article is then heated to decompose the peroxyl or azo free radical initiator to form free radicals and produce crosslinks in the synthetic thermoplastic resin having a crystalline melting temperature of 100° C. or higher. The heating step is preferably carried out in an oxygen-deficient atmosphere. For purposes of the present invention, an oxygen-deficient atmosphere is a gas containing 1 mole percent or less of molecular oxygen (O2). The oxygen-deficient atmosphere may contain 0.1 mole percent or less of molecular oxygen. The oxygen-deficient atmosphere may contain 98 mole percent or more, preferably 99 mole percent or more, more preferably 99.9 mole percent or more of an inert gas, such as nitrogen, argon, carbon dioxide, steam, helium, or a mixture of any two or more thereof.
[0052] The temperature during this heating step is equal to or greater than 70°C and less than the crystalline melting temperature of the synthetic thermoplastic resin, or, in the case of fabrics, less than the fiber melting temperature as determined according to the applicable method of ASTM D7138-16. The article remains in a solid state during the heating step and exhibits no or negligible change to its original dimensions and geometry. Preferred temperatures are equal to or greater than 80°C, or equal to or greater than 90°C, up to 150°C, or up to 125°C.
[0053] The heating step is preferably carried out in the substantial absence of ionizing radiation, such as UV radiation, e-beam radiation, or other ionizing radiation, at up to 1 kGy, up to 0.1 kGy, up to 0.01 kGy, etc. It is particularly preferred that the article is not exposed to such ionizing radiation during the heating step, except as may be present due to natural background radiation.
[0054] The pressure during the heating step may be subatmospheric, atmospheric or superatmospheric, with superatmospheric pressures being advantageous, such as a pressure of 689 kPa to 6895 kPa gauge (100 to 1000 psi gauge).
[0055] The heating step may continue for, for example, 1 minute or more, 15 minutes or more, or 30 minutes or more. Periods longer than 2 hours are generally unnecessary but can be used if more crosslinking is required or the article is large or thick. During the heating step, the free radical initiator generates free radicals. The free radicals and polyene crosslink the synthetic thermoplastic resin. Crosslink density generally increases with increasing heating time.
[0056] Crosslinking typically results in changes in the physical and / or thermal properties of the polyamide and / or polyester components of the article. The crosslinked synthetic thermoplastic components may exhibit, among others, one or more of i) non-melting behavior typical of thermosets, ii) delayed ignition, and / or iii) reduced dripping when exposed to an open flame.
[0057] Mechanical properties may also change somewhat as a result of crosslinking. Fabrics treated according to the present invention often show a significant reduction in dripping when subjected to flame tests such as ASTM D6413-11, EN 13501-1 Single Burning Item test and British Standard BS5867 Part 2-Type B test. Fabrics treated according to the present invention often show slight changes in properties such as air flow, "hand", drapeability, etc.
[0058] Various optional components of the coating composition, or their reaction products, may remain with the treated article and form a coating on the treated article, or in some cases may penetrate the synthetic thermoplastic components of the article, or both. Certain carriers, if present, may remain with the treated article and impart functional properties to the treated article. The terminal vinyl polysiloxane may polymerize and / or graft to the synthetic thermoplastic resin under the conditions of step (b) to impart elasticity.
[0059] The following examples are intended to illustrate, but not limit, the scope of the invention. All parts and percentages are by weight unless otherwise indicated. Example 1 47.5 parts of triallyl isocyanurate and 500mm nominal viscosity 2 A coating composition is prepared by mixing 47.5 parts of a vinyl terminated polysiloxane polymer having an OH group content of 0.15 mmol / g and a vinyl content of 0.15 mmol / g with 5 parts azobisiso(butyronitrile) in a high shear mixer.
[0060] The coating composition is applied to each side of each of the following fabrics using a gravure coater at about 35° C. to 40° C. The total weight of both coatings is about 0.3 kg per kg of fabric. The amount of triallyl isocyanurate applied is about 0.1425 kg per kg of fabric, and the amount of azobis(butyronitrile) applied is about 0.015 kg per kg of fabric.
[0061] Fabric A: 98:2 blend of nylon 6,6 and spandex in camouflage color, fabric weight 144 g / m 2 . Fabric B: 100% nylon 6,6 in camouflage color, fabric weight 48 g / m 2 .
[0062] Fabric C: 100% nylon 6,6 in grey, fabric weight 50 g / m 2 . Fabric D: 100% acrylic, fabric weight 287g / m 2 . Fabrics A, B, and C each exhibit a fiber melting temperature, as measured according to ASTM D7138-16, greater than 150° C. Nylon 6,6 itself has a crystalline melting temperature greater than 150° C.
[0063] After coating, the fabric is then heat treated in an autoclave at 100° C. for 1 hour under 400 psig of nitrogen (oxygen content less than 100 ppm) to create crosslinks in the nylon.
[0064] Treated and untreated fabric samples are evaluated for breathability in a DA Atlas M021A Air Permeability Tester and for water repellency using the AATCC TM-022 Spray Test.
[0065] The treated fabrics are also subjected to a Vertical Flame Drip Test as follows: A 3 inch by 12 inch fabric sample is hung vertically. A 1.5 inch high flame is placed under the bottom edge of the sample and allowed to ignite for 12 seconds before being removed. The sample is observed for flammability and melting / dripping during burning.
[0066] Each of the untreated fabrics melts and drips under the conditions of the Vertical Flame Drop Test. After treatment, no melting or dripping is observed on any of the fabric samples. In addition, all fabrics show a large improvement in water repellency, increasing from a rating of 0 to 70 for fabric A, and from a rating of 0 to 100 for fabrics B and C. All fabrics show a slightly decreased breathability.
[0067] Example 2 47 parts of triallyl isocyanurate and a nominal viscosity of 500 mm 2 25 parts of a vinyl terminated polysiloxane polymer having a vinyl content of 0.15 mmol / g and a nominal viscosity of 1000 mm 2 A coating composition is prepared by mixing 24 parts of poly(dimethylsiloxane) having a 1:1 / s ratio with 3 parts of azobisiso(butyronitrile) in a high shear mixer.
[0068] The coating composition is applied to each side of each of Fabric A and Fabric B using a gravure coater at about 23° C. The total weight of both coatings is about 0.3 kg per kg of fabric. The amount of triallyl isocyanurate applied is about 0.14 kg per kg of fabric, and the amount of azobis-suis (butyronitrile) applied is about 0.009 kg per kg of fabric. After coating, the fabric is heat treated in an autoclave at 100° C. for 30 minutes under nitrogen (oxygen content less than 100 ppm) at 400 psig (2.76 MPa) gauge pressure to produce crosslinks in the nylon.
[0069] Treated and untreated fabric samples are evaluated for breathability, water repellency and performance in the Vertical Burning Drop Test. As previously mentioned, each of the untreated fabrics melts and drips under the conditions of the Vertical Burn Drop Test. After treatment, no melting or dripping is observed on any of the fabric samples, even after being subjected to 20 wash cycles.
[0070] The water repellency spray rating of Fabric A increased from zero to 60 and dropped to 50 after undergoing 20 wash cycles. The air permeability of untreated Fabric A was 3.49 L / s (7.2 standard cubic feet per minute), which remained essentially unchanged after treatment. The air permeability of the treated fabric dropped to 1.98 L / s (4.2 CFM) after 20 wash cycles.
[0071] The water repellency spray rating of Fabric B increases from 0 to 60 after treatment. The breathability decreases from 11.0 L / s (23.3 CFM) to 8.07 L / s (17.1 CFM) after treatment and further decreases to 6.04 L / s (12.8 CFM) after 20 wash cycles.
[0072] Example 3 Separate samples of Fabric A are treated on each side with one of the following coating compositions and heat treated for 30 minutes to produce crosslinks in the fabric as described in the previous examples.
[0073] Composition 3A: 37 parts of triallyl isocyanurate and a 500 mm nominal viscosity 2 20 parts of a vinyl terminated polysiloxane polymer having a vinyl content of 0.15 mmol / g and a nominal viscosity of 1000 mm 2 / s, 19.5 parts poly(dimethylsiloxane), 2.5 parts azobisiso(butyronitrile) and 20 parts melamine cyanurate.
[0074] Composition 3B: 37 parts of triallyl isocyanurate and a 500 mm nominal viscosity 2 20 parts of a vinyl terminated polysiloxane polymer having a vinyl content of 0.15 mmol / g and a nominal viscosity of 1000 mm 2 / s, 19.5 parts azobisiso(butyronitrile), and 2.5 parts melamine polyphosphate.
[0075] The amount of triallyl isocyanurate applied in each case is about 0.111 kg per kg of fabric, and the amount of azobis(butyronitrile) is about 0.0075 kg per kg of fabric.
[0076] None of the treated samples show melting or dripping in the flame test. The breathability is 11.0 L / s (7.2 CFM) for the untreated sample and only slightly decreases to 2.83 L / s (6.2 CFM) and 3.21 L / s (6.8 CFM) for the samples treated with Compositions 3A and 3B, respectively. The water repellency rating is 50 in each case.
[0077] Example 4 46.5 parts of triallyl isocyanurate and 500mm nominal viscosity 2 A coating composition is prepared by mixing 46.5 parts of a vinyl terminated polysiloxane polymer having an OH group content of 0.15 mmol / g and a vinyl content of 0.15 mmol / g with 5 parts azobisiso(butyronitrile) in a high shear mixer.
[0078] Such coating composition is applied at about 23°C on a poly(ethylene terephthalate) fabric having a weight of 139 grams per square meter and heated for 1 hour as described in the previous examples to produce crosslinks in the resin. The amount of triallyl isocyanurate applied is about 0.1395 kg per kg of fabric, and the amount of azobis(butyronitrile) is about 0.015 kg per kg of fabric. Such fabric has a melting temperature greater than 150°C as measured according to ASTM D7138-16. Untreated fabric melts and drips under a vertical flame test, whereas treated fabric does not exhibit melting or dripping. The air permeability of the treated fabric is 176 L / s (373 CFM) compared to 187 L / s (397 CFM) for untreated fabric.
[0079] Comparative samples A and B Each side of Fabric A and Fabric B is coated with a coating composition and cured in the same general manner as described in the previous examples. The coating composition is generally as described in U.S. Patent Application Publication No. 2017 / 0029663 and contains 38% octadecyl acrylate, 11% 1,6-hexanediol diacrylate, 5% dipentaerythritol pentaacrylate, 3% lauryl peroxide, and 10% ethyl acetate having a nominal viscosity of 10 mm. 2 and 43% non-terminated vinyl poly(dimethylsiloxane) having a viscosity of 10C St / s. Such compositions contain only 14% by weight of polyene (1,6-hexanediol and dipentaerythritol pentaacrylate). In each case, the total amount of polyene applied to both coatings combined is about 0.048 kg per kg of fabric, and the total amount of lauryl peroxide is about 0.009 kg per kg of fabric. Fabrics thus treated melt and drip when subjected to a vertical burn test. The large amount of octadecyl acrylate and poly(dimethylsiloxane) in the coating composition is believed to adversely affect the ability of the composition to introduce crosslinks into the fabric, even if a significant amount of polyene and free radical initiator are provided with the coating.
[0080] Examples 5A-5C Separate samples of Fabric B were treated on each side with one of the following coating compositions at various coating weights as shown in the table below, and heat treated for 30 minutes to produce crosslinks in the fabric in the manner described in the previous examples. The treated samples were subjected to the burn, spray and breathability tests described above, with the results shown in the table.
[0081] Composition 5A: 92 parts triallyl isocyanurate and 8 parts lauroyl peroxide. Composition 5B: 94 parts triallyl isocyanurate and 6 parts lauroyl peroxide. Composition 5C: 96 parts triallyl isocyanurate and 4 parts lauroyl peroxide.
[0082] [Table 1]
[0083] *Not an example of the present invention. The data in the table shows the effect of the amount of free radical initiator applied. Application amounts less than 0.005 kg per kg of fabric are insufficient. Even an application amount of 0.006 kg per kg provides a slight benefit in Sample 5B, but the equivalent amount of free radical initiator applied provides good results at higher overall coating weights.
[0084] Example 6 Each side of Fabric D is coated with a coating composition containing 92.6% triallyl isocyanurate and 7.4% lauroyl peroxide on each side. The total coating weight (both sides) is 0.1 kg / kg. The coating weight of the polyene is 0.0926 kg / kg and the coating weight of the lauroyl peroxide is 0.0074 kg / kg. Then, the fabric is stretched for 500 mm. 2100 / s of terminated vinyl polysiloxane is applied over the polyene / free radical initiator on each side, also at a total coating weight of 0.1 kg / kg. The coated fabric is then cured at 135°C for 30 minutes under nitrogen pressure of 400 psig and an oxygen level of less than 100 ppm. No melting is observed in a flame test. The treated fabric has a spray rating of 70 and an air permeability of 28.4 cubic feet per minute (L / s).
[0085] Similar results are seen when the polysiloxane coating weight is increased to 0.15 kg / kg.
Claims
1. 1. A solid-state method for treating a synthetic thermoplastic article comprising a synthetic thermoplastic component, the thermoplastic component comprising one or more synthetic thermoplastic resins having a crystalline melting temperature of 100° C. or greater, the method comprising: a) applying a coating composition to one or more surfaces of the article at a temperature below the crystalline melting temperature of the synthetic thermoplastic resin to contact one or more synthetic thermoplastic components of the article, the coating composition comprising: i) from 30 to 99.9 weight percent, based on the weight of the coating composition, of one or more polyene compounds having 2 to 6 vinyl groups and a vinyl equivalent of 125 g / eq or less; and (ii) one or more free radical initiators, wherein the coating composition is applied to the article in an amount sufficient to provide at least 0.04 kg of polyene compound and at least 0.005 kg of peroxy or azo free radical initiator per kg of polyamide component, polyester component, or both in the article; b) heating the coated article to a temperature of at least 70° C. and below the crystalline melting temperature of the synthetic thermoplastic resin to decompose the peroxy or azo free radical initiator to form free radicals and generate crosslinks in the synthetic thermoplastic resin.
2. 10. The solid state method of claim 1, wherein the synthetic thermoplastic component comprises one or more of an aliphatic polyamide, a polyester, and a polyacrylonitrile.
3. 3. The solid state process of claim 2, wherein the synthetic thermoplastic component comprises one or more thermoplastic aliphatic polyamide resins selected from the group consisting of nylon 4, nylon 6, nylon 8, nylon 9, nylon 10, nylon 12, nylon 4 / 6, nylon 5 / 6, nylon 6 / 6, nylon 6 / 9, nylon 10 / 10, and nylon 10 / 12.
4. 3. The solid state method of claim 2, wherein the synthetic thermoplastic component comprises one or more thermoplastic polyester resins selected from the group consisting of poly(ethylene terephthalate), poly(butylene terephthalate), poly(ethylene adipate-co-terephthalate), poly(butylene adipate-co-terephthalate), poly(ethylene succinate), poly(1,4-cyclohexylene-dimethylene terephthalate), and poly(butylene succinate).
5. 3. The solid state method of claim 2, wherein the synthetic thermoplastic component comprises one or more thermoplastic polyacrylonitriles.
6. 2. The solid state process of claim 1, wherein the synthetic thermoplastic article is a fabric, the fabric comprising fibers made from a synthetic thermoplastic resin having a crystalline melting temperature of 100° C. or greater, either alone or in a blend with fibers made from a polymer other than a synthetic thermoplastic resin having a crystalline melting temperature of 100° C. or greater, the fibers having a melting temperature of 100° C. or greater as measured according to ASTM D7138-16.
7. 1. A solid state method for reducing melting, dripping, or both, of a fabric, the fabric comprising fibers, either alone or in blends with fibers, of a polymer other than a synthetic thermoplastic resin, having a crystalline melting temperature of 100° C. or greater, the fibers having a melting temperature of 100° C. or greater as measured according to ASTM D7138-16, the method comprising: a) applying a coating composition to one or more surfaces of the fabric at a temperature below the melting temperature of the fibers, the coating composition comprising: i) from 30 to 99.9 weight percent, based on the weight of the coating composition, of one or more polyene compounds having 2 to 6 vinyl groups and a vinyl equivalent weight of 125 g / eq or less; and (ii) one or more free radical initiators, wherein a sufficient amount of the coating composition is applied to the article to provide at least 0.04 kg of polyene compound and at least 0.005 kg of peroxy or azo free radical initiator per kg of fabric; b) heating the coated fabric to a temperature above 70° C. and below the melting temperature of the fibers for a period of 1 minute to 2 hours.
8. 8. The solid phase method of claim 7, wherein the synthetic thermoplastic resin is one or more of an aliphatic polyamide, a polyester, and a polyacrylonitrile.
9. 9. The solid phase method of claim 8, wherein the aliphatic polyamide is selected from the group consisting of nylon 4, nylon 6, nylon 8, nylon 9, nylon 10, nylon 12, nylon 4 / 6, nylon 5 / 6, nylon 6 / 6, nylon 6 / 9, nylon 10 / 10 and nylon 10 / 12.
10. 9. The solid phase method of claim 8, wherein the synthetic thermoplastic resin is selected from the group consisting of poly(ethylene terephthalate), poly(butylene terephthalate), poly(ethylene adipate-co-terephthalate), poly(butylene adipate-co-terephthalate), poly(ethylene succinate), poly(1,4-cyclohexylene-dimethylene terephthalate), and poly(butylene succinate).
11. 9. The solid phase method of claim 8, wherein the synthetic thermoplastic resin is polyacrylonitrile.
12. The polyene compound may be 1,4-butanediol diacrylate, 1,5-pentanediol diacrylate, 1,6-hexanediol diacrylate, neopentyl glycol diacrylate, diethylene glycol diacrylate, triethylene glycol diacrylate, tetraethylene glycol diacrylate, polyethylene glycol diacrylate, dipropylene glycol diacrylate, tripropylene glycol diacrylate, cyclohexanedimethanol diacrylate, alkoxylated hexanediol diacrylate, neopentyl glycol diacrylate, propoxylated neopentyl glycol diacrylate, trimethylolpropane triacrylate, ethoxylated ethyloxylated and / or propoxylated glycerin triacrylate, pentaerythritol di-, tri- or tetraacrylate, erythritol di-, tri- or tetraacrylate, acrylated polyester oligomer, bisphenol A diacrylate, acrylated bisphenol A diglycidyl ether, ethoxylated bisphenol A diacrylate, tris(2-hydroxyethyl)isocyanurate triacrylate oligomer, acrylated urethane oligomer, 1,4-butanediol diallyl ether, 1,5-pentanediol diallyl ether, 1,6-hexanediol diallyl ether, neopentyl glycol diallyl ether, diethylene glycol diallyl ether, triethylene glycol diallyl ether, tetraethylene glycol diallyl ether, polyethylene glycol diallyl ether, dipropylene glycol diallyl ether, tripropylene glycol diallyl ether, cyclohexanedimethanol diallyl ether, alkoxylated hexanediol diallyl ether, neopentyl glycol diallyl ether, propoxylated neopentyl glycol diallyl ether, trimethylolpropane di- or triallyl ether, ethoxylated trimethylolpropane di- or triallyl ether, propoxylated trimethylolpropane di- or triallyl ether, The solid phase method according to any one of claims 1 to 11, wherein the glyceryl group is one or more of propane di- or triallyl ether, glycerin di- or triallyl ether, ethoxylated and / or propoxylated glycerin di- or triallyl ether, pentaerythritol di-, tri- or tetra-allyl ether, erythritol di-, tri- or tetra-allyl ether, acrylated polyester oligomer, bisphenol A diacrylate, acrylated bisphenol A diglycidyl ether, ethoxylated bisphenol A diallyl ether, diallyl maleate, diallyl fumarate, diallyl phthalate, diallyl terephthalate, diallyl succinate, di- or triallyl citrate, triallyl cyanurate and triallyl isocyanurate.
13. The solid phase process according to any one of claims 1 to 12, wherein the free radical initiator constitutes 2% to 8% of the total weight of the coating composition.
14. The solid phase method according to any one of claims 1 to 13, wherein the coating composition further comprises a terminal vinyl polysiloxane having 0.1 mmol to 2 mmol of vinyl groups per gram.
15. 15. The solid phase method of claim 14, wherein the coating composition comprises 5 to 50% by weight of the terminal vinyl polysiloxane having 0.1 mmol to 2 mmol of vinyl groups per gram.
16. 16. The solid phase process of claim 14 or 15, wherein the polyene compound, the free radical initiator, and the vinyl-terminated polysiloxane having 0.1 mmol to 2 mmol of vinyl groups per gram collectively constitute 50% to 100% of the total weight of the coating composition.
Citation Information
Patent Citations
Method of modification of property of formed product
JP1977045677A
Method of growing amorphous substance
JP1989010622A
Locking and release confirmation device
JP1996013868A
Fiber structure
JP2007146313A
Flame-retardant composition and flame-retardant base material
JP2019131764A